HUMAN CAPITAL DALAM PERSPEKTIF MANAJEMEN STRATEGIS: INTEGRASI INVESTASI MODAL MANUSIA TERHADAP KEUNGGULAN KOMPETITIF ORGANISASI - Laysah Putri; Riska Amelia; Selvi Nopi Yanti; Marnis Marnis (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The paradigm shift in modern management, from viewing labor as merely an operational cost to recognizing it as a strategic organizational asset, has transformed the way companies create competitive advantage. This literature review article aims to analyze the integration of human capital within the perspective of strategic management and its influence on organizational competitiveness, particularly in facing digital transformation and global economic crises. The study was conducted using a systematic literature review method based on various primary references relevant to strategic human resource management. The findings indicate that investment in human capital through education, training, and competency development significantly contributes to improving productivity, organizational commitment, and corporate adaptability. Human capital is no longer perceived solely as an administrative function, but rather as a component of Strategic Human Capital (SHC) that possesses high value, rarity, and inimitability compared to competitors. Furthermore, Human Capital Disclosure (HCD) in public companies has become an important indicator for investors and stakeholders in assessing organizational sustainability. This study emphasizes that the integration of proactive human resource policies with flexible business strategies constitutes a fundamental basis for maintaining organizational competitive advantage in the era of Industry 4.0.